The Kompilasi Hukum Islam in Indonesia: Compilation and Its Relation to Islamic Jurispridence [Kompilasi Hukum Islam di Indonesia: Penyusunan dan Kaitannya dengan Ushul Fikih] - Sulfanwandi Sulfanwandi (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: Based on the constitutional law, the legal basis for KHI is still weak because it places KHI in an unwritten legal position, plus the material for KHI is separate from the Presidential Instruction. Besides that, the position of KHI as a guide in litigation places judges and the community seeking justice not to be bound by it. Therefore, theoretically, KHI still cannot provide legal certainty which is the demand of modern Indonesian society. Thus, the contribution of Islamic law in the development of national law is becoming increasingly far from expectations. Furthermore, in terms of its effectiveness in the community, it needs to be reviewed further. This is due to a misunderstanding in society which states that Islamic law is only found in Islamic law books. Whereas Islamic law books are only one part of Islamic law. Alongside it is the fatwas of the ulama, the laws and regulations of Muslim countries, and the decisions of the Religious Courts. Therefore, it is necessary to socialize KHI in the community as well as to make efforts to correct the misunderstanding of Islamic law. Abstrak: Dilihat dari hukum tata negara, landasan hukum KHI itu masih lemah karena menempatkan KHI dalam posisi hukum yang tidak tertulis ditambah lagi materi KHI terpisah dari lnpres tersebut. Di samping itu posisi KHI sebagai pedoman dalam berperkara menempatkan hakim dan masyarakat pencari keadilan untuk tidak terikat padanya. Oleh karena itu, secara teoritis KHI tetap saja tidak bisa memberi kepastian hukum yang merupakan tuntutan masyarakat Indonesia modern. Dengan demikian sumbangsih hukum Islam dalam pembinaan hukum nasional menjadi semakin jauh dari harapan. Selanjutnya dari segi efektivitasnya di masyarakat perlu ditinjau lebih lanjut. Hal ini disebabkan oleh adanya pemahaman yang keliru dalam masyarakat yang menyatakan bahwa hukum Islam itu hanya terdapat dalam kitab-kitab fikih . Padahal kitab-kitab fikih merupakan satu bagian saja dari hukum Islam. Di sampingnya terdapat fatwa-fatwa ulama, peraturan perundang-undangan negeri-negeri muslim, dan keputusan Pengadilan Agama. Oleh karena itu diperlukan sosialisasi KHI di masyarakat sekaligus diperlukan usaha-usaha untuk meluruskan kekeliruan pemahaman terhadap hukum Islam tersebut.